Impact of exogenous thiamine on Kluyveromyces marxianus under oenological conditions - Labuschagne, Pieter Willem Jacobus (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.